Critically high metal ion levels found in metal-on-metal modular hinged knee arthroplasty: a comparison of two different systems. (1st March 2022) - Gramlich, Yves; Hofmann, Line; Kress, Sandra; Ruckes, Christian; Kemmerer, Matthias; Klug, Alexander; Hoffmann, Reinhard; Kremer, Michael
Abstract : Aims: This study compared the cobalt and chromium serum ion concentration of patients treated with two different metal-on-metal (MoM) hinged total knee arthroplasty (TKA) systems, as well as a titanium nitride (TiN)-coated variant. Methods: A total of 63 patients (65 implants) were treated using either a MoM-coated (n = 29) or TiN-coated (n = 7) hinged TKA (GenuX mobile bearing, MUTARS; Implantcast, Germany) versus the BPKS (Brehm, Germany) hinged TKA (n = 27), in which the weight placed on the MoM hinge is diffused through a polyethylene (PE) inlay, reducing the direct load on the MoM hinge. Serum cobalt and chromium ion concentrations were assessed after minimum follow-up of 12 months, as well as functional outcome and quality of life. Results: No differences in mean age (69 years, 40 to 86), mean age adapted Charlson Comorbidity Index (3.1 (SD 1.4)), mean BMI (29.2 kg/m 2 (SD 5.8)), or number of other implants were observed between groups. Significant improvements in outcome scores and pain levels were achieved for all groups, and there was no difference in quality of life (12-Item Short-Form Health Survey questionnaire (SF-12)). Mean cobalt and chromium ion levels were significantly higher for the GenuX versus the BPKS hinged TKA (GenuX vs BPKS: cobalt: 16.3 vs 9.4 µg/l; chromium: 9.5 vs 5.2 µg/l). The TiN-coated implants did not appear to confer improvement in the metal ion levels. Metal ion concentrations above 7 µg/l were detected in 81%(29/36) of GenuX patients versus 41% (11/27) in the BPKS group. No GenuX patients had normal levels under 2 µg/l, versus 22% of BPKS patients. No significant reduction in outcome scores was observed regardless of the metal ion levels, whereas higher work-related activity was correlated with higher chromium concentrations. Conclusion: Hinged TKA, using MoM hinges, resulted in critically high cobalt and chromium ion concentrations. The BPKS hinged TKA showed significantly lower metal ion concentrations compared with the GenuX TKA. No benefits were observed using TiN coating. The different weightbearing mechanics might influence the wear of the component materials. Higher workloads and physical activity could influence chromium levels. Cite this article: Bone Joint J 2022;104-B(3):376–385.